PERSEPSI ATLET ANGGAR KOTA PEKANBARU TERHADAP LATIHAN MELALUI METODE VIRTUAL - Kevin Fadillah; Ramadi Ramadi; Ali Mandan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The purpose of this study was conducted to find out the perceptions of athletes according to the trainers and athletes of the city of Pekanbaru fencing towards training through virtual methods. This research was conducted using a type of quantitative descriptive research. The data in this study are primary data, namely data obtained directly from the respondents in the form of the results of the fencing practice perception test during the virtual method. The time in the research process was carried out in May-July 2021. The instrument used in this research was a closed questionnaire. Based on the results of the research and discussion that the authors have described in the previous chapter, it can be concluded that the results of the perception data of fencing athlete training through the virtual city of Pekanbaru method are in the Very Low category of 13 athletes and 2 coaches. It can be seen from the statistical figures showing the results of the standard deviation of 26.9 while the highest score is 80 and the lowest score is 20. Therefore the quality of the athlete's fencing is very low during virtual training. Then the results of the analysis are seen from the results of the frequency numbers which show that there are 13 athletes whose results are low, which means that there are 13 athletes who are in a low position, virtual training greatly affects the quality of the Fencing athletes in Pekanbaru City. Key Words: Perception of Fencing Athletes, Virtual Training